2014
DOI: 10.1159/000362643
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Response in a Patient with del(5q) Myelodysplastic Syndrome Who Discontinued Lenalidomide and Obtained a Good Response and Tolerance to Rechallenge

Abstract: Background: The introduction of the immunomodulatory drug lenalidomide has revolutionized the treatment of patients with myelodysplastic syndromes (MDS) and deletion of the long arm of chromosome 5. Treatment with lenalidomide results in transfusion independence in the majority of patients, but some questions remain unresolved, among them the duration of treatment. Moreover, a number of unexpected long-term remissions in patients who stopped lenalidomide for various reasons have been observed. Case Report: We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 13 publications
(19 reference statements)
1
1
0
Order By: Relevance
“…In a small patient series, drug discontinuation after having achieved complete cytogenetic remission was associated with prolonged responses [17] with patients who relapsed to transfusion dependence responding to reexposure of lenalidomide. A similar observation has been reported [18] in a patient with isolated del(5q) MDS who was treated with lenalidomide, achieved complete hematologic and cytogenetic remission and relapsed to transfusion dependence after a 14-month treatment interruption. A durable hematologic response was observed after reexposure to lenalidomide, but cytogenetic response was not as profound as after the initiation of lenalidomide.…”
Section: Acknowledgmentssupporting
confidence: 84%
“…In a small patient series, drug discontinuation after having achieved complete cytogenetic remission was associated with prolonged responses [17] with patients who relapsed to transfusion dependence responding to reexposure of lenalidomide. A similar observation has been reported [18] in a patient with isolated del(5q) MDS who was treated with lenalidomide, achieved complete hematologic and cytogenetic remission and relapsed to transfusion dependence after a 14-month treatment interruption. A durable hematologic response was observed after reexposure to lenalidomide, but cytogenetic response was not as profound as after the initiation of lenalidomide.…”
Section: Acknowledgmentssupporting
confidence: 84%
“…Although it was recently shown that lenalidomide treatment in MDS del(5q) patients does not appear to increase the risk to AML transformation (14), other long-term effects of immunomodulation have not been elucidated and one could argue that intermittent use of lenalidomide may be prudent is certain cases. The present case indicated that durable hematological response may be sustained despite discontinuation of lenalidomide, whereas others have shown that re-challenge may also be safe and feasible, albeit with no profound cytogenetic response (15). However, in order to draw safe conclusions regarding the treatment duration and time of discontinuation, a randomized clinical trial is required to compare continuous treatment until progression, vs. treatment discontinuation after having achieved sustained complete cytogenetic response.…”
Section: Discussionmentioning
confidence: 78%